Determination of Acceptable Inertia Limit for Ensuring Adequacy Under High Levels of Wind Integration - Chavez-Orostica, H (IEEE Computer Society, 2014)
The significant penetration of wind generation in power grids has raised new challenges in operational and planning decisions of power systems. Wind turbine units almost always include power converters decoupling the frequency dynamics of the wind power generators from that of the grid. This decoupling causes a reduction in total system inertia, affecting the system s ability to overcome frequency disturbances [1]. To study the impact of wind power on system inertia, a system identification approach is followed. This heuristic identification method determines the parameters of governors and prime movers. The instantaneous minimum frequency requirements and the rate of change of frequency are simulated using the identified power system, and via an extrapolation, the maximum wind power penetration in Sweden is found. Finally, a need for market design is introduced in order to ensure adequacy. © 2014 IEEE.